The Resolution of International Trade Disputes through Arbitration - Nufaris Elisa (Britain International for Academic Research (BIAR) Publisher, 2020)
If an international trade dispute occurs, so that the ways of resolution can be reached through non-litigation (alternative litigation) or Alternative Dispute Resolution (ADR). The facilities classified as ADR other than Arbitration facilities as contained in Article 6 of Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution which includes facilities including Meditation facilities, Negotiation facilities, Consolidation facilities, and other facilities. Based on the Arbitration Law it provides an opportunity to resolve trade disputes through the Arbitration institution and it is very appropriate if this institution has a very important role in resolving disputes that occur in the world of international trade. The scope of disputes which can be tried in a trial of the International Commercial Arbitration institution must be related to the issue of trade, finance and general trading (commerce), while those relating to other matters have nothing to do at all.